Arsenic Trioxide-based Nanomedicines as a Therapeutic Combination Approach for Treating Gliomas: A Review - Siddique, Rabeea; Khan, Suliman; Bai, Qian; Li, Hongmin; Ullah, Muhammad W.; Xue, Mengzhou (Current Nanoscience, 2021)
Glioblastoma is one of the fatal and aggressive types of brain tumors. The current standard treatment for glioblastoma multiform (GBM) is surgical resection coupled with radiotherapy and chemotherapy. Although ample research has been performed, and multiple novel pharmacological approaches have been investigated for developing effective therapeutic drugs for treating GBM, the success of extending the survival of the patient is notably low. The unique barrier limiting GBM treatment is the presence of the blood-brain barrier (BBB), and most of the chemotherapeutic drugs fail to cross it due to their high molecular weight and large size. The currently used chemo drugs for GBM have poor penetration ability to the brain and cause off-target toxicity due to a high dose for maintaining drug concentration at the tumor site. The use of nanomaterial composites for co-delivery of multiple therapeutic drugs offers several advantages by encompassing the aforementioned obstacles. In this review, the first part sheds light on the characteristics of GBM and the major challenges faced by the current pharmacological treatments. The second part emphasizes the application of nanomaterials- based nanotherapeutics to overcome the challenges associated with current GBM therapy. A closer look is given to the use of FDA approved traditional Chinese medicine arsenic trioxide (ATO) and its application as co-delivery nanoparticles (i.e., ATO-NPs) against solid tumors, especially gliomas. In short, a breakthrough in nanotechnology offers a promising platform to treat GBM; however, rigorous efforts need to be devoted in order to develop novel therapeutic drugs with higher therapeutic efficiency and limited side effects.
Keywords: solid tumor